2016
DOI: 10.3389/fphar.2016.00107
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Proteases: Modes of Activation and Future Prospects as Pharmacological Targets

Abstract: Proteolytic enzymes are crucial for a variety of biological processes in organisms ranging from lower (virus, bacteria, and parasite) to the higher organisms (mammals). Proteases cleave proteins into smaller fragments by catalyzing peptide bonds hydrolysis. Proteases are classified according to their catalytic site, and distributed into four major classes: cysteine proteases, serine proteases, aspartic proteases, and metalloproteases. This review will cover only cysteine proteases, papain family enzymes which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
183
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(195 citation statements)
references
References 79 publications
(116 reference statements)
2
183
1
9
Order By: Relevance
“…3.1. The inhibition of MERS-CoV and SARS-CoV PL pro s by disulfiram PL pro s are cysteine proteases that use the thiol group of cysteine as a nucleophile to attack the carbonyl group of the scissile peptide bond Han et al, 2005;Verma et al, 2016). Inhibition can be expected if the catalytic cysteine of a PL pro is interfered with or modified (Cheng et al, 2015;Chou et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…3.1. The inhibition of MERS-CoV and SARS-CoV PL pro s by disulfiram PL pro s are cysteine proteases that use the thiol group of cysteine as a nucleophile to attack the carbonyl group of the scissile peptide bond Han et al, 2005;Verma et al, 2016). Inhibition can be expected if the catalytic cysteine of a PL pro is interfered with or modified (Cheng et al, 2015;Chou et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Cathepsin L‐like enzymes have a propeptide including 100 residues consists of a short β strand (β1) and three α‐helices (α1, α2, α3) forming similar super‐secondary structure with cathepsin B‐like enzymes (Fig. C) . Taking cathepsin K as an example, the S2′ and S1′ subsites are occupied by Met75 and Thr76, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The protease activity was found to be optimal at low pH of 4 which is the crucial factor to activate Papain like cysteine proteases (Richau et al, 2012;Sundararaj et al, 2012). A number of reports have shown that cysteine proteases can be auto catalytically activated in vitro from zymogen to mature enzyme even at reduced pH (Lowther et al, 2009;Sundararaj et al, 2012;Verma et al, 2016) indicating it to be a cysteine protease. In an attempt to validate the nature of the protease we used various inhibitors to monitor its activity.…”
Section: Discussionmentioning
confidence: 99%
“…To further know the active site residue involved in the interaction between HEV-protease with inhibitors, its 3D structure has been modeled which also showed the nature of the HEVprotease. The predicted model showed two domains architecture, N-terminal helix and C-terminal β-sheet domain similar to papain-like cysteine proteases (Verma et al, 2016) but differ in arrangement of secondary structure elements. An active site (catalytic pocket) for substrate binding was present between two domains.…”
Section: In Silico Analysis Of Hev-proteasementioning
confidence: 92%